Multimodal and Reflective Pedagogies in Enhancing EFL Academic Presentation Skills: A Case Study - Rika Andayani; Hanip Pujiati; Imas Wahyu Agustina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Academic presentation skills are crucial components of academic literacy in English as a Foreign Language (EFL) context, yet many students continue to experience challenges in delivering effective academic presentations. This study explores how EFL students’ academic presentation skills are enhanced through classroom-based instructional practices. Employing a qualitative case study design, the research was conducted in an undergraduate EFL classroom at English Education Study Program, Universitas Negeri Jakarta, Indonesia. Data were collected through classroom observations, students’ academic presentation videos, reflective journals, and semi-structured interviews. The data were analyzed thematically to identify patterns related to students’ skill enhancement over the course of the instructional process. The findings reveal that students’ academic presentation skills were enhanced through iterative presentation practice, explicit instruction on presentation structure and language use, and reflective activities that encouraged self-awareness and peer feedback. In addition, the integration of visual and verbal resources supported students’ confidence and clarity in presenting academic content. This study highlights the importance of pedagogically structured support and reflective learning in enhancing EFL students’ academic presentation skills. The findings offer practical insights for EFL lecturers seeking to design effective academic presentation instruction and contribute to the growing body of qualitative research on academic literacy development in higher education.